PERFIL DE LOS MEDICAMENTOS QUE SE REGISTRARON EN COSTA RICA DURANTE EL PERÍODO 2018-2023 - Blanco Barrantes, Jeimy (2024)
The Ministry of Health is responsible for protecting and promoting public health, and one of its main duties is to ensure compliance with regulations. Authorities responsible for health regulations authorize the sale of medicines through a health registration process, which ensures the safety, effectiveness, and quality of these products. Between 2018 and 2023, in Costa Rica there were 1657 requests for analysis of the first lot of commercialization, with an average of 276 products per year. In 86% of the cases, there was already a registered pharmaceutical equivalent and only 14% had some advantage or innovation, such as new active ingredients that have never been commercialized in Costa Rica or products designed to offer advantages over previous versions. 6% of the analyzed products corresponded to new active ingredients, 6% to a new presentation, and 2% to a new combination. Understanding the profile of the medicines registered in the country is necessary to analyze the health situation and improve accessibility, quality, and equity of health services.